Insights into ENGO activities in the Salish Sea: A call for more coordination, communication, and potential for communities of practice. Issue 133 (July 2022) - Jones, Jacob; Keller, C. Peter; van der Flier Keller, Eileen
Abstract: This paper contributes to analysis of missions of environmental non-government organizations (ENGOs) in environmental stewardship. The literature identifies a diversity of roles including tension between ENGOs working directly with government to participate in decision making processes and exerting influence on government through public education and direct action. We offer additional insights and note a shift in missions over time by reporting on a case study of missions and activities of environmental non-governmental organizations (ENGOs) focusing on the conservation and protection of the transboundary waters of the Salish Sea marine environment. The case study is based on a survey of 119 ENGO websites and interviews with 17 environmental ENGO leaders. We note growing awareness of the value of efforts in education and strategic communication initiatives, both internally and externally, and comment on challenges with transboundary collaborations. We propose opportunities for better coordination, notably across the international border. We also call for investment in communities of practice to support, among other things, awareness-raising and communication, data sharing, and advancing the role of creativity and the arts to foster environmental stewardship.